Technical efficiency analysis of the conversion of cropland to forestland program in Jiangxi, Shaanxi, and Sichuan. Issue 6 (18th August 2019) - Ma, Oliver Z.; Wang, Guangyu; Wang, Guibin; Wang, Liguo; Chen, Baozhang; Mi, Feng; Shrestha, Anil; Eshpeter, Sarah; Pang, Yong; Liu, Shirong; Guo, Xiaomin; Innes, John L.
ABSTRACT: Conversion of Cropland to Forestland Program (CCFP) has greatly impacted China's agricultural sector, and more specifically rural farmers. While changes in living standards as a result of the implementation of the CCFP have been analyzed, little research has been conducted regarding the impacts of such policies on farming operations. As agriculture contributes nearly 10% of national GDP, it is important to analyze the implications of policies on a national industry. An input-oriented data envelopment analysis (DEA) model was used to examine the technical efficiency of farming operations following implementation of the CCFP, using survey data from farmers in Jiangxi, Shaanxi, and Sichuan provinces. Additionally, the impact of factors such as urbanization, age and education, and land fragmentation was examined with respect to farming operational efficiency. Scale inefficiency was found to have the greatest effect on overall inefficiency in farming operations in comparison to pure technical inefficiency, which was largely influenced by the presence and degree of land fragmentation of land holdings. Findings can be used to inform national land-use policies facilitating land fragmentation in China and address gaps in existing broader level studies that utilize non-parametric approaches to examine the technical efficiency of Chinese farmers affected by the CCFP.